Depression, Anxiety, and Stress Among People With Chronic Hepatitis C Virus Infection and a History of Injecting Drug Use in New South Wales, Australia. Issue 1 (January 2017) - Fortier, Emmanuel; Alavi, Maryam; Bruneau, Julie; Micallef, Michelle; Perram, Jacinta; Sockalingam, Sanjeev; Dunlop, Adrian J.; Balcomb, Annie C.; Day, Carolyn A.; Treloar, Carla; Bath, Nicky; Haber, Paul S.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aims of this study were to assess symptoms of depression, anxiety, and stress and associated sociodemographic factors among people living with chronic hepatitis C virus (HCV) infection with a history of injecting drug use and to assess the association between symptoms of depression, anxiety, or stress and HCV treatment intent, specialist assessment, or treatment uptake. Methods: The Enhancing Treatment for Hepatitis C in Opioid Substitution Settings was an observational cohort study evaluating the provision of HCV assessment and treatment among people with chronic HCV and a history of injecting drug use, recruited from 9 community health centers and opioid substitution therapy (OST) clinics (New South Wales, Australia). Symptoms were assessed using the Depression Anxiety Stress Scales (DASS-21). Analyses were performed using logistic regression. Results: Among 415 participants (mean age 41 years, 71% male), 47%, 52%, and 36% demonstrated moderate to extremely severe symptoms of depression, anxiety, and stress, respectively. In adjusted analyses, depression symptoms were associated with recent injecting drug use [adjusted odds ratio (aOR) 1.63, 95% confidence interval (CI) 1.07–2.49), whereas stress symptoms were associated with unemployment (aOR 2.99, 95% CI 1.09–8.15) and not living with a spouse or other relatives/friends (aOR 1.55, 95% CI 1.01–2.39). Symptoms of depression, anxiety, or stress or having a history of treated mental illness were not independently associated with HCV treatment intent, specialist assessment, or treatment uptake. Conclusions: Findings suggest a need for improved interventions and care regarding mental health among people living with chronic HCV with a history of injecting drug use, but suggest that symptoms of depression, anxiety, and stress should not be immediate contraindications to HCV assessment and treatment.